Air Temperature Control System In Silent Generator Box - Anif Saukon Kamalul Husna; Desriyanti Desriyanti; Rhesma Intan Vidyastari (Muhammadiyah University, Sidoarjo, 2021)
For the community, generators are an alternative if there is a power outage or if there is a large enough electricity demand. According to workers in the field of generator rental in Trenggalek, namely